Teaching Model of Academic Writing with Process-Genre Approach to Enhancing University Students' Critical Thinking Skills - Helaluddin Helaluddin; Duwi Purwati; Muhammad Guntur; Hasmawaty Hasmawaty; Hengki Wijaya (UICELL, 2022)
Writing, one of the productive skills, is a language skill teachers need to pay more attention to. When teaching her writing skills, the teacher must develop a learning model based on the student’s needs. This study aims to develop and test an academic writing learning model based on a process-genre approach to improve students’ critical thinking skills. Researchers use a research and design (R&D) approach related to 4D theory, which consists of four main phases: definition, design, development, and dissemination. The research was conducted at UIN Sultan Maulana Hasanuddin Banten with participants from a student group, lecturers and two expert persons. This result indicates that the learning model using the process-genre approach proved to be valid, practical, and effective in improving students’ critical thinking skills. With these findings, each lecturer will be able to develop their learning model according to the needs of their students and lecturers so that they can support efforts to achieve their expected goals. Keywords: academic writing, critical thinking skills, process-genre approach, teaching models